Benomyl sensitivity of isolates of Colletotrichum acutatum and C. gloeosporioides from citrus - Peres, N. A R [UNESP]; Souza, N. L. [UNESP]; Peever, T. L.; Timmer, L. W. (Scientific Societies, 2004)
Postbloom fruit drop (PFD) of citrus, caused by Colletotrichum acutatum, produces orange-brown lesions on petals and results in premature fruit drop and the retention of calyces. C. gloeosporioides is common in groves and causes postharvest anthracnose on fruit. Both diseases are controlled effectively by the fungicide benomyl in research fields and commercial orchards. Highly sensitive and resistant isolates of C. gloeosporioides were found, whereas all isolates of C. acutatum tested were moderately resistant. In preliminary studies conducted in vitro with three isolates of each, mycelial growth of sensitive isolates of C. gloeosporioides was inhibited completely by benomyl (Benlate 50 WP) at 1.0 μg/ml, whereas resistant isolates grew well at 10 μg/ml. Growth of all isolates of C. acutatum was inhibited by about 55% at 0.1 μg/ml and by 80% at 1.0 μg/ml. Spore germination of C. acutatum was inhibited more at 0.1 μg/ml than at 1.0 μg/ml or higher concentrations. In all, 20 isolates of C. acutatum from 17 groves and 20 isolates of C. gloeosporioides from 7 groves were collected from locations with different histories of benomyl usage in São Paulo, Brazil, and Florida, United States. Benomyl at 1.0 μ.g/ml completely inhibited growth of 133 isolates of C. gloeosporioides, with the exception of 7 isolates that were highly resistant to the fungicide, whereas all isolates of C. acutatum were only partially inhibited at 0.1 and 1.0 μg/ml. Analysis of variance indicated that the sensitivity of the isolates of C. acutatum was not affected by benomyl usage or grove of origin, and country of origin had only minor effects. No highly resistant or sensitive isolate of C. acutatum was recovered. Partial sequencing of the β-tubulin gene did not reveal nucleotide substitutions in codons 198 or 200 in C. acutatum that usually are associated with benomyl resistance in other fungi.
Keywords: Disease control; Fruits; Genes; Harvesting; Substitution reactions; Petals; Plants (botany); Bacteria (microorganisms); Citrus; Colletotrichum; Fungi; Glomerella acutata; Glomerella cingulata